Manajemen Rekam Medis Dalam Temu Kembali Dokumen Di Rumah Sakit Haji Medan - Muhammad Rasyad Ghazali (Jurnal Pustaka Nusantara dan Budaya, 2013)
This research are purposed to know proceed of management and storage for medical record and document retrieval at Medan Haji Hospital. This research are done in sub part of take a bord of patient medical record of Medan Haji Hospital. This research is part of descriptive kualitative research by using data collecting method through by interview. The main source which are using by the chief of medical record and a staff medical record at Medan Haji Hospital. The result of research, are got that life cycle of management medical record at Medan Haji Hospital have been done basicly guiding book. Which are got Medan Haji Hospital, numbering system of medical record at Medan Haji Hospital is basicly on unit numbering system which consist of six digit, storage system have been sentralitation. Equalitation system use direct numbering system. Hospital wisdom an equalization shelf have not been implementated because most patient are over 100 of a day. This case have made shelf exploded. Now the arrangement only on type of payment, month and year patient to take medical. The result of analysis based on kind payment, mont, year to make medical which are there on unit medical record are still unadequate and will be run staff working productivity slowly especially storage shelving which must be replaced